A Critical Appraisal of Madhu-Ghṛta Prashana from Ayurvedic Texts in the Context of Physiological Juandice - S Panicker, Meera; G, Arathi; Sathian, Saritha; Kuril, Vd Aarti Bharatlal; Chalak, Rohini (Journal of Neonatal Surgery, 2025)
Introduction: Neonatal hyperbilirubinemia is a common clinical condition encountered during the neonatal period, particularly in the first week of life. It is estimated that approximately 8% to 11% of neonates develop some degree of hyperbilirubinemia. Elevated bilirubin levels, if not properly managed, can be toxic to the central nervous system (CNS) and may result in long-term neurological impairments, such as kernicterus.The most prevalent form is physiological jaundice, which arises due to the immaturity of the liver and other physiological systems involved in bilirubin metabolism and excretion. While typically self-limiting, early intervention is essential in preventing complications. In traditional Ayurvedic literature, various newborn care practices are described under the term Jatakarma Samskaras, a series of rituals and health-promoting procedures performed immediately after birth. One such practice is Madhu-Ghrita Prashana—the administration of a small quantity of honey and clarified butter (ghee) to the newborn. This paper aims to explore the scientific basis for this traditional practice and evaluate its potential role in supporting neonatal liver function and possibly reducing the severity or early onset of physiological jaundice. Materials and Methods: The literary review done from the various classical Ayurvedic literatures and paediatric textbooks. Critical review also done from articles published in various journals. Results and Discussion: Though physiological jaundice doesn’t have any serious consequences; it can create concern in the physician and anxiety in the parents. Madhu and grta prashana mentioned in neonatal care suggest an early initiation of feeding along with ensuring a coordinated sucking and swallowing reflex in the newborn. Apart from these benefits it also can help in addressing various physiological immaturities leading to the development of physiological jaundice in a neonate. Conclusion: Samskaras are series of rituals performed at different stages of human life. These rituals performed possess some socio -cultural as well as some scientific rational behind it. Jatakarma samskaras helps the newborn to adapt to the new environment for further survival. The physiological handicaps of a newborn can be improved by the madhu and grta prashana thereby preventing the rise of bilirubin to a major extent.